Genome-wide autosomal, mtDNA, and Y chromosome analysis of King Bela III of the Hungarian Arpad dynasty - Chuan-Chao Wang (Nature Portfolio, 2021)
Abstract The ancient Hungarians, “Madzsars”, established their control of the Carpathian Basin in the late ninth century and founded the Hungarian Kingdom around 1000AD. The origin of the Magyars as a tribal federation has been much debated in the past. From the time of the conquest to the early fourteenth century they were ruled by descendants of the Arpad family. In order to learn more about the genetic origin of this family, we here analyzed the genome of Bela III one of the most prominent members of the early Hungarian dynasty that ruled the Hungarian Kingdom from 1172 to 1196. The Y-Chromosome of Bela III belongs to haplogroup R1a-Z2123 that is today found in highest frequency in Central Asia, supporting a Central Asian origin for the ruling lineage of the Hungarian kingdom. The autosomal DNA profile of Bela III, however, falls within the genetic variation of present-day east European populations. This is further supported through his mtDNA genome that belongs to haplogroup H, the most common European maternal lineage, but also found in Central Asia. However, we didn’t find an exact haplotype match for Bela III. The typical autosomal and maternal Central Eastern European ancestry among Bela III autosomes might be best explained by consecutive intermarriage with local European ruling families.